Difference between revisions of "009B Sample Final 1, Problem 7"

From Math Wiki
Jump to navigation Jump to search
 
(2 intermediate revisions by the same user not shown)
Line 1: Line 1:
::<span class="exam">a) Find the length of the curve
+
<span class="exam">(a) Find the length of the curve
  
::::::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}.</math>
+
::<math>y=\ln (\cos x),~~~0\leq x \leq \frac{\pi}{3}</math>.
  
::<span class="exam">b) The curve
+
<span class="exam">(b) The curve
  
::::::<math>y=1-x^2,~~~0\leq x \leq 1</math>
+
::<math>y=1-x^2,~~~0\leq x \leq 1</math>
  
:::<span class="exam">is rotated about the <math style="vertical-align: -3px">y</math>-axis. Find the area of the resulting surface.
+
<span class="exam">is rotated about the &nbsp;<math style="vertical-align: -3px">y</math>-axis. Find the area of the resulting surface.
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Foundations: &nbsp;  
 
!Foundations: &nbsp;  
 
|-
 
|-
|Recall:
+
|'''1.''' The formula for the length &nbsp;<math style="vertical-align: 0px">L</math>&nbsp; of a curve &nbsp;<math style="vertical-align: -5px">y=f(x)</math>&nbsp; where &nbsp;<math style="vertical-align: -3px">a\leq x \leq b</math>&nbsp; is
 
|-
 
|-
 
|
 
|
::'''1.''' The formula for the length <math style="vertical-align: 0px">L</math> of a curve <math style="vertical-align: -5px">y=f(x)</math> where <math style="vertical-align: -3px">a\leq x \leq b</math> is
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math>  
 
|-
 
|-
|
+
|'''2.''' Recall
:::<math>L=\int_a^b \sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math>
 
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp; <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math>
::'''2.''' <math style="vertical-align: -14px">\int \sec x~dx=\ln|\sec(x)+\tan(x)|+C.</math>
 
 
|-
 
|-
|
+
|'''3.''' The surface area &nbsp;<math style="vertical-align: 0px">S</math>&nbsp; of a function &nbsp;<math style="vertical-align: -5px">y=f(x)</math>&nbsp; rotated about the &nbsp;<math style="vertical-align: -4px">y</math>-axis is given by  
::'''3.''' The surface area <math style="vertical-align: 0px">S</math> of a function <math style="vertical-align: -5px">y=f(x)</math> rotated about the <math style="vertical-align: -4px">y</math>-axis is given by  
 
 
|-
 
|-
 
|
 
|
:::<math style="vertical-align: -13px">S=\int 2\pi x\,ds</math>, where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -13px">S=\int 2\pi x\,ds,</math>&nbsp; where <math style="vertical-align: -18px">ds=\sqrt{1+\bigg(\frac{dy}{dx}\bigg)^2}~dx.</math>
 
|}
 
|}
 +
  
 
'''Solution:'''
 
'''Solution:'''
Line 37: Line 35:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|First, we calculate&thinsp; <math>\frac{dy}{dx}.</math>  
+
|First, we calculate &nbsp;<math>\frac{dy}{dx}.</math>  
 
|-
 
|-
|Since <math style="vertical-align: -5px">y=\ln (\cos x),</math>
+
|Since &nbsp;<math style="vertical-align: -5px">y=\ln (\cos x),</math>
 
|-
 
|-
|
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{dy}{dx}=\frac{1}{\cos x}(-\sin x)=-\tan x.</math>
::<math>\frac{dy}{dx}=\frac{1}{\cos x}(-\sin x)=-\tan x.</math>
 
 
|-
 
|-
 
|Using the formula given in the Foundations section, we have
 
|Using the formula given in the Foundations section, we have
 
|-
 
|-
 
|
 
|
::<math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>L=\int_0^{\pi/3} \sqrt{1+(-\tan x)^2}~dx.</math>
 
|}
 
|}
  
Line 53: Line 50:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we have:
+
|Now, we have
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\
 
L & = & \displaystyle{\int_0^{\pi/3} \sqrt{1+\tan^2 x}~dx}\\
 
&&\\
 
&&\\
Line 73: Line 70:
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
 
L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\
 
L& = & \ln |\sec x+\tan x|\bigg|_0^{\frac{\pi}{3}}\\
 
&&\\
 
&&\\
Line 82: Line 79:
 
& = & \displaystyle{\ln (2+\sqrt{3})}.
 
& = & \displaystyle{\ln (2+\sqrt{3})}.
 
\end{array}</math>
 
\end{array}</math>
 +
|-
 +
|
 
|}
 
|}
  
Line 89: Line 88:
 
!Step 1: &nbsp;  
 
!Step 1: &nbsp;  
 
|-
 
|-
|We start by calculating&thinsp; <math>\frac{dy}{dx}.</math>  
+
|We start by calculating &nbsp;<math>\frac{dy}{dx}.</math>  
 
|-
 
|-
|Since <math style="vertical-align: -13px">y=1-x^2,~ \frac{dy}{dx}=-2x.</math>
+
|Since &nbsp;<math style="vertical-align: -5px">y=1-x^2,</math>
 +
|-
 +
|&nbsp; &nbsp; &nbsp; &nbsp;<math>\frac{dy}{dx}=-2x.</math>
 
|-
 
|-
 
|Using the formula given in the Foundations section, we have
 
|Using the formula given in the Foundations section, we have
 
|-
 
|-
 
|
 
|
::<math>S\,=\,\int_0^{1}2\pi x \sqrt{1+(-2x)^2}~dx.</math>
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>S\,=\,\int_0^{1}2\pi x \sqrt{1+(-2x)^2}~dx.</math>
 
|}
 
|}
  
Line 102: Line 103:
 
!Step 2: &nbsp;
 
!Step 2: &nbsp;
 
|-
 
|-
|Now, we have <math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math>
+
|Now, we have &nbsp;<math style="vertical-align: -14px">S=\int_0^{1}2\pi x \sqrt{1+4x^2}~dx.</math>
 
|-
 
|-
|We proceed by using trig substitution. Let <math style="vertical-align: -13px">x=\frac{1}{2}\tan \theta.</math> Then, <math style="vertical-align:  -12px">dx=\frac{1}{2}\sec^2\theta \,d\theta.</math>
+
|We proceed by &nbsp;<math>u</math>-substitution.  
 
|-
 
|-
|So, we have
+
|Let &nbsp;<math style="vertical-align: -2px">u=1+4x^2.</math> &nbsp;
 
|-
 
|-
|
+
|Then, &nbsp; <math style="vertical-align: 0px">du=8xdx</math>&nbsp; and &nbsp;<math style="vertical-align: -14px">\frac{du}{8}=xdx.</math>
::<math>\begin{array}{rcl}
+
|-
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int 2\pi \bigg(\frac{1}{2}\tan \theta\bigg)\sqrt{1+\tan^2\theta}\bigg(\frac{1}{2}\sec^2\theta\bigg) d\theta}\\
+
|Since the integral is a definite integral, we need to change the bounds of integration.
&&\\
+
|-
& = & \displaystyle{\int \frac{\pi}{2} \tan \theta \sec \theta \sec^2\theta d\theta}.\\
+
|Plugging in our values into the equation &nbsp;<math style="vertical-align: -4px">u=1+4x^2,</math>&nbsp; we get
\end{array}</math>
 
|}
 
 
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Step 3: &nbsp;
 
 
|-
 
|-
|Now, we use <math style="vertical-align: 0px">u</math>-substitution. Let <math style="vertical-align: 0px">u=\sec \theta.</math> Then, <math style="vertical-align: -1px">du=\sec \theta \tan \theta \,d\theta.</math>
+
|&nbsp; &nbsp; &nbsp; &nbsp;<math style="vertical-align: -5px">u_1=1+4(0)^2=1</math>&nbsp; and &nbsp;<math style="vertical-align: -5px">u_2=1+4(1)^2=5.</math>
 
|-
 
|-
|So, the integral becomes
+
|Thus, the integral becomes
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
\displaystyle{\int 2\pi x \sqrt{1+4x^2}~dx} & = & \displaystyle{\int \frac{\pi}{2}u^2du}\\
+
S& = & \displaystyle{\int_1^5 \frac{2\pi}{8} \sqrt{u}~du}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi}{6}u^3+C}\\
+
& = & \displaystyle{\frac{\pi}{4} \int_1^5 u^{\frac{1}{2}}~du.}
&&\\
 
& = & \displaystyle{\frac{\pi}{6}\sec^3\theta+C}\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{6}(\sqrt{1+4x^2})^3+C}.\\
 
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
!Step 4: &nbsp;
+
!Step 3: &nbsp;
 
|-
 
|-
|We started with a definite integral. So, using Step 2 and 3, we have
+
|Now, we integrate to get
 
|-
 
|-
 
|
 
|
::<math>\begin{array}{rcl}
+
&nbsp; &nbsp; &nbsp; &nbsp;<math>\begin{array}{rcl}
S & = & \displaystyle{\int_0^1 2\pi x \sqrt{1+4x^2}~dx}\\
+
\displaystyle{S} & = & \displaystyle{\frac{\pi}{4}\bigg(\frac{2}{3}u^{\frac{3}{2}}\bigg)\bigg|_{1}^{5}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi}{6}(\sqrt{1+4x^2})^3}\bigg|_0^1\\
+
& = & \displaystyle{\frac{\pi}{6}u^{\frac{3}{2}}\bigg|_{1}^{5}}\\
 
&&\\
 
&&\\
& = & \displaystyle{\frac{\pi(\sqrt{5})^3}{6}-\frac{\pi}{6}}\\
+
& = & \displaystyle{\frac{\pi}{6}(5)^{\frac{3}{2}}-\frac{\pi}{6}(1)^{\frac{3}{2}}}\\
 
&&\\
 
&&\\
 
& = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\
 
& = & \displaystyle{\frac{\pi}{6}(5\sqrt{5}-1)}.\\
 
\end{array}</math>
 
\end{array}</math>
 
|}
 
|}
 +
  
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
{| class="mw-collapsible mw-collapsed" style = "text-align:left;"
 
!Final Answer: &nbsp;  
 
!Final Answer: &nbsp;  
 
|-
 
|-
|'''(a)''' &nbsp;<math>\ln (2+\sqrt{3})</math>
+
|&nbsp; &nbsp; '''(a)''' &nbsp; &nbsp;<math>\ln (2+\sqrt{3})</math>
 
|-
 
|-
|'''(b)''' &nbsp;<math>\frac{\pi}{6}(5\sqrt{5}-1)</math>
+
|&nbsp; &nbsp; '''(b)''' &nbsp; &nbsp;<math>\frac{\pi}{6}(5\sqrt{5}-1)</math>
 
|}
 
|}
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]
 
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']]

Latest revision as of 17:06, 20 May 2017

(a) Find the length of the curve

.

(b) The curve

is rotated about the  -axis. Find the area of the resulting surface.

Foundations:  
1. The formula for the length    of a curve    where    is

       

2. Recall
       
3. The surface area    of a function    rotated about the  -axis is given by

         where


Solution:

(a)

Step 1:  
First, we calculate  
Since  
       
Using the formula given in the Foundations section, we have

       

Step 2:  
Now, we have

       

Step 3:  
Finally,

       

(b)

Step 1:  
We start by calculating  
Since  
       
Using the formula given in the Foundations section, we have

       

Step 2:  
Now, we have  
We proceed by  -substitution.
Let    
Then,     and  
Since the integral is a definite integral, we need to change the bounds of integration.
Plugging in our values into the equation    we get
         and  
Thus, the integral becomes

       

Step 3:  
Now, we integrate to get

       


Final Answer:  
    (a)    
    (b)    

Return to Sample Exam